Serious hemorrhages after ischemic stroke or TIA - Incidence, mortality, and predictors. - Joachim Ögren; Anna-Lotta Irewall; Lars Söderström; Thomas Mooe (PLoS ONE, 2018)
Data are lacking on the risk and impact of a serious hemorrhage on the prognosis after ischemic stroke (IS) or transient ischemic attack (TIA). We aimed to estimate the incidence of serious hemorrhage, analyze the impact on mortality, and identify predictors of hemorrhage after discharge from IS or TIA.All patients admitted to Östersund Hospital for an IS or TIA in 2010-2013 were included (n = 1528, mean age: 75.1 years). Serious hemorrhages were identified until 31st December 2015. Incidence rates were calculated. The impact on mortality (stratified by functional level) was determined with Kaplan-Meier analysis. Non-parametric estimation under the assumption of competing risk was performed to assess the cumulative incidence and predictors of serious hemorrhages. The incidence rates of serious (n = 113) and intracranial hemorrhages (n = 45) after discharge from IS and TIA were 2.48% and 0.96% per year at risk, respectively. Patients with modified Rankin Scale (mRS) scores of 3-5 exhibited 58.9% mortality during follow-up and those with mRS scores of 0-2 exhibited 18.4% mortality. A serious hemorrhage did not affect mortality in patients with impaired functional status, but it increased the risk of death in patients with mRS scores of 0-2. Hypertension was associated with increased risk of serious hemorrhage.We found that, after discharge from an IS or TIA, serious hemorrhages were fairly common. Impairments in function were associated with high mortality, but serious hemorrhages only increased the risk of mortality in patients with no or slight disability. Improved hypertension treatment may decrease the risk of serious hemorrhage, but in patients with low functional status, poor survival makes secondary prevention challenging.